A Novel Thermo‐Polymerizable Aromatic Diamine: Synthesis and Application in Enhancement of the Properties of Conventional Polyimides. Issue 7 (4th February 2016) - Luo, Yijie; Sun, Jing; Wang, Jiajia; Jin, Kaikai; He, Fengkai; Fang, Qiang
Abstract : Owing to their important application in the production of high performance materials, aromatic diamines have received interest in many areas for several years. However, most of the polymers derivated from diamines show poor processability due to their rigid backbone. Although much effort has been made, a balance between the solvent (or heat)‐resistance and processability of the polymers still needs to be achieved. In this contribution, a new aromatic diamine is reported, which has both reactive amine groups and thermo‐polymerizable benzocyclobutene moieties. Starting from the diamine can not only give the corresponding polymers, such as polyamides, polyimides, and polyurethanes, but can also provide new structural materials through the post‐polymerization of the polymers. It is found that adding diamine into a conventional polyimide system can greatly improve the properties of the polyimide, such as T g, coefficient of thermal expansion, tensile strength, and storage modulus. When the content of the diamine is in the range ≈ 5–10 mol%, the tensile strength of the conventional polyimide is increased by up to 30%. The highest T g (> 400 °C) is observed when the content of the diamine is 40 mol%. Abstract : A novel aromatic diamine having both of reactive amine groups and directly thermo‐polymerizable benzocyclobutene moiety is successfully synthesized. It is used to modify the properties of the conventional polyimides, making a great improvement of the properties of the polyimides such as Tg, coefficient of thermal expansion, tensile strength, and storage modulus.